Microbiological Bacteria Analysis of Salted White Snapper Fish Sold in Ternate City - Isra Abuba; Ahmad Talib; Ibnu W Laitupa; Azis Husen (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2024)
This research was conducted in the market in Ternate City for sampling salted white snapper and for the microbiological testing process carried out at the Class I Babullah Ternate Fish Quarantine Station in March 2024, with the aim of knowing the safety level of salted white snapper products in Ternate City and to identify microbial content in salted white snapper products. The working method used is to conduct microbiological testing of Salmonella sp bacteria using (ISO 6579: 2015) on salted white snapper fish samples obtained from the three markets in Ternate City. The results showed that the test results of salted white snapper fish in Dufa-Dufa Market, Gamalama Market, Bastiong Market were negative for Salmonella bacteria and the results of pre-enrichment tests, enrichment tests and biochemical tests of Salmonella sp bacteria in salted white snapper fish in Dufa-Dufa Market, Gamalama Market, Bastiong Market were negative for Salmonella bacteria. While the advice from the author is that the results of the research that has been done can be suggested for salted fish traders who are sold by further improving cleanliness at the place of sale, equipment and the traders themselves so that contamination of salted fish can be minimized.